Komunikasi Politik Perspektif Islam - Armadila Armadila (Al-Balagh : Jurnal Komunikasi Islam, 2023)
Islam views a power with a transcendent explanation, power includes these things that are required to be accountable to the Creator. Humans do not act arbitrarily in using their authority because humans are the extension of the hand of the creator in the universe. A ruler in Islamic teachings is a head of state who knows how to give mass properly, so that the message and content conveyed has a good effect on people, a good head of state is more than a ruler who knows how to communicate with the community and understand their own qualities. Have the ability and also understand that leaders must be according to God's will and work under His guidance. Good communication from a good leader is by using the six guidelines of the Qur'an, namely sadida rules, baligha rules, ma'rufa rules, karima rules, service rules and social rules. Proficient in making many kinds of decisions based on what has been outlined by Islam are the characteristics of a commendable head of state, not only changing an individual Muslim, but also being wise to lead the global community in this era.